Fundamental data compression - Pu, Ida Mengyi (Oxford ; Burlington, MA : Butterworth-Heinemann, 2006)
Fundamental Data Compression provides all the information students need to be able to use this essential technology in their future careers. A huge, active research field, and a part of many people's everyday lives, compression technology is an essential part of today's Computer Science and Electronic Engineering courses. With the help of this book, students can gain a thorough understanding of the underlying theory and algorithms, as well as specific techniques used in a range of scenarios, including the application of compression techniques to text, still images, video and audio. Practical exercises, projects and exam questions reinforce learning, along with suggestions for further reading. * Dedicated data compression textbook for use on undergraduate courses * Provides essential knowledge for today's web/multimedia applications * Accessible, well structured text backed up by extensive exercises and sample exam questions.
Coding symbolic data -- Run-length algorithms -- Huffman coding -- Adaptive Huffman coding -- Arithmetic coding -- Dictionary-based compression -- Prediction and transforms -- Audio compression -- Image compression -- Video compression.
Includes bibliographical references and index.
Keywords: Data compression (Computer Science).; Algorithms; Computer algorithms; Electronic books